2011
DOI: 10.5897/ajbm11.1313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender on credit card usage among university students in Turkey

Abstract: In recent years, much has been written about credit card usage among university students. Despite a vast number of studies little has been written about credit card usage among university students in developing countries. This research surveyed university students in Turkey in an attempt to understand their uses of credit cards. In particular, we examined the impact of gender on credit card use. The literature on the impact of gender on credit card usage is a bit unsettled and this study seeks to add another d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Additionally, researchers found that since respondents have been using credit cards wisely, the use of credit cards would provide supports and will not cause to financial problems in the future. Ucal et al (2011) examined effects of gender on credit card usage among university students in Turkey. They employed both parametric and nonparametric measures to measure the effects of gender on credit card usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, researchers found that since respondents have been using credit cards wisely, the use of credit cards would provide supports and will not cause to financial problems in the future. Ucal et al (2011) examined effects of gender on credit card usage among university students in Turkey. They employed both parametric and nonparametric measures to measure the effects of gender on credit card usage.…”
Section: Literature Reviewmentioning
confidence: 99%